Pfeifer-Weber-Christian disease and successful treatment with mycophenolate mofetil: a case report. Issue 5 (22nd May 2019) - Somalanka, Subash; Udo, Ini; Nair, Hari; Baikunje, Shashidhar
Abstract : Inflammatory conditions manifest with a broad spectrum of signs and symptoms. Panniculitis is such a condition affecting the subcutaneous fat and presents as tender erythematous nodules. It is also associated with a systemic response and has been described in the literature as early as in 1892 by Pfeifer and in the 1920s by Weber and Christian. We present an unusual case of a Caucasian man with recurrent febrile illness, systemic inflammatory response and renal dysfunction requiring acute high dependency care. The authors successfully treated him with an antiproliferative agent, mycophenolate mofetil, which resulted in preventing him from having further episodes.